A Comparison of Corporate Governance and Tax Avoidance of UK and Japanese Firms - Bassem Salhi; Jabr Al Jabr; Anis Jarboui (Comparative Economic Research, 2020)
The present study was designed to determine the relationship between corporate governance and tax avoidance in an international setting. Financial and governance data sourced from the Datastream database for a sample of Japanese and UK firms between 2012 and 2017 are used. First, we examine the direct effect of several corporate governance mechanisms on tax avoidance. Second, we divide the full sample into two groups (common law and code law legal system) to explore the relationship between law, corporate governance, and tax avoidance. We use both univariate and feasible generalized least square (FGLS) regression methods to examine our hypotheses. This study finds that the board size, independent directors, and the presence of women on boards of directors reduce the likelihood of tax avoidance. However, we find an insignificant association between ownership concentration and tax avoidance. Second, it also finds that firms in countries with higher country-level governance engage in less tax avoidance. The results also suggest that the role of corporate governance is more pronounced for firms operating in common law countries than those in code law countries. This manuscript is one of the few studies that examine the relationship between corporate governance and tax avoidance in an international setting with different legal and institutional environment. This relationship differs across the two countries. This paper clearly identifies implications for research, practice, and society. It documents that when a country implements a good system of governance, which targets improving transparency and accountability, it will lead to less corporate tax avoidance.